2020
DOI: 10.1158/1078-0432.ccr-19-0353
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Associated Fibroblasts Promote HER2-Targeted Therapy Resistance through FGFR2 Activation

Abstract: Purpose: Despite the therapeutic success of existing HER2-targeted therapies, tumors invariably relapse. This study aimed at identifying new mechanisms responsible for HER2-targeted therapy resistance. Experimental Design: We have used a platform of HER2-targeted therapy–resistant cell lines and primary cultures of healthy and tumor-associated fibroblasts (TAF) to identify new potential targets related to tumor escape from an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 46 publications
2
65
0
Order By: Relevance
“…Tissue from all specimens was minced into small pieces and digested to further isolate the fibroblast population. 9 The obtained fibroblasts were seeded in 10% of FBS-DMEM medium and cultured under standard conditions (37°C under a humidified atmosphere with 5% CO 2 ). The purity of the CAFs was evaluated by morphological assessments and immunofluorescence analyses of α-smooth muscle actin (Supplementary Figure S1A).…”
Section: Cell Lines and Culturesmentioning
confidence: 99%
“…Tissue from all specimens was minced into small pieces and digested to further isolate the fibroblast population. 9 The obtained fibroblasts were seeded in 10% of FBS-DMEM medium and cultured under standard conditions (37°C under a humidified atmosphere with 5% CO 2 ). The purity of the CAFs was evaluated by morphological assessments and immunofluorescence analyses of α-smooth muscle actin (Supplementary Figure S1A).…”
Section: Cell Lines and Culturesmentioning
confidence: 99%
“…(2019) (Truong et al, 2019). A large number of studies documented the effects of CAF cells on morphology changes of various types of cancer cells (Fernandez-Nogueira et al, 2019;Miyazaki et al, 2019;Yu et al, 2014;Zhuang et al, 2015).…”
mentioning
confidence: 99%
“…Human breast cancer-associated (CAF-173, CAF-200, CAF-220 and CAF-318) and normal fibroblasts (RMF-31 and RMF-39) were derived from human breast tumours and reduction mammoplasty surgeries respectively, immortalized, tagged with GFP and cultured in collagen pre-coated flasks 34 . The aforementioned human mammary fibroblasts, TS1 cells derived from primary tumours of the MMTV-PyMT mice model 27,75 , LM2 breast cancer cells (kindly donated by Dr. Roger Gomis) and HS27 skin fibroblasts (kindly donated by Dr. Ander Izeta) were cultured in DMEM medium supplemented with 10% fetal bovine serum (FBS), 1% glutamine, and 1% penicillin and streptomycin.…”
Section: Methodsmentioning
confidence: 99%
“…Depletion of OSMR in the tumour microenvironment resulted in delayed tumour onset and tumour growth ( As we previously observed that fibroblasts were the cell population with higher levels of OSMR within the stroma (Fig. 3), we performed complementary in vitro and in vivo experiments to assess the effect of OSMR activation in mammary cancer-associated and normal fibroblasts derived from human breast tumours and reduction mammoplasty surgeries 34 , respectively. The ability to remodel the extracellular matrix is a hallmark of CAFs 25 .…”
Section: Stromal Osmr Deletion Hampers Tumour Progression and Aggressmentioning
confidence: 99%